2021
DOI: 10.2147/prbm.s335022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gender-Based Emotional Intelligence in Corporate Financial Decision-Making

Abstract: Purpose Business competition is getting more intense nowadays, and corporate survival is getting harder; consequently, corporate managers have to make financial decisions in complex and globalized scenarios. As a result, in order to compete in today’s global economy, businesses are contemplating incorporating behavioural components of human psychology into their decision-making processes. Corporations are masters of quantitative analysis, but they rarely pay attention to behavioural elements of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 72 publications
0
26
0
1
Order By: Relevance
“…The findings revealed that emotional intelligence and linguistic achievement are inextricably linked. Previous studies have also shown that emotional intelligence has a positive impact on academic attainment (Ran et al, 2021). In another study, the relationship between emotional intelligence and English language learning was investigated (Paul Sun and Jun Zhang, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that emotional intelligence and linguistic achievement are inextricably linked. Previous studies have also shown that emotional intelligence has a positive impact on academic attainment (Ran et al, 2021). In another study, the relationship between emotional intelligence and English language learning was investigated (Paul Sun and Jun Zhang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a positive viewpoint might influence how social bonds are perceived. Students who regularly interpret themselves, others, and life events in a favorable light have a higher opinion of social relationships ( Ran et al, 2021 ). As a result, it is logical to believe that learners who have a good attitude are less likely to have foreign language classroom anxiety (FLCA; Jin and Dewaele, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a skill that can be learnt, developed, and enhanced. According to Salovey and Mayer (1990) , emotional intelligence involves an “ability to monitor one’s own and others’ moods and emotions, to distinguish among them and to utilize this information to direct one’s thinking and actions.” A related definition adds the “capacity to perceive, express, regulate, and manage emotions in an adaptive manner.” Age, developmental level, and gender have all been demonstrated to influence personal or emotional intelligence ( Ran et al, 2021 ). Moreover, our attitude and perspective on life are influenced by emotional intelligence.…”
Section: Research Literaturementioning
confidence: 99%
“…Authority, by correlation, is opposed to adaptation. Numerous organizations have neglected to increment and guarantee authoritative profitability, bringing about great governance, even though they had talented staff and the correct workplace (Ran et al, 2021 ). Business leaders in these organizations have not had the option to spur their kin by actualizing significant worker motivation (Kirkland et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%